Inclusive Education for Special Needs Students in Indonesia: A Review of Policies, Practices and Challenges - Somad, Abdul; Haryanto, Sigit; Darsinah, Darsinah (Graduate Program Magister Manajemen Pendidikan, 2024)
This review research study focuses on reviewing the existing policies, methods, and challenges pertaining to inclusive education for special needs students in Indonesia. Following the formulation of appropriate research inquiries at the onset of the study, the researchers conducted extensive searches throughout prominent research databases utilizing certain keywords. Following a comprehensive evaluation, a total of 145 pertinent elements were identified. Subsequently, the researchers systematically reviewed each manuscript and excluded those that were not pertinent to the primary objective of the study. In order to fulfil the specified criteria, the studies were required to be composed in the English language, accessible to a wide range of individuals from 2017 to 2023. Furthermore, these studies were expected to provide explicit responses to the inquiries posed by the researchers, with a particular emphasis on students with special needs, mostly those enrolled in elementary school. The ultimate selection consisted of a compilation of 22 distinct research articles. There is a growing recognition among individuals that the fulfilment of educational requirements for special needs students within inclusive environments holds significant importance. Implementing inclusive policies poses significant challenges due to various factors, including insufficient teacher training, limited availability of resources, and the absence of standardized methods for identifying special needs individuals. There is a recommendation to conduct further study in order to identify optimal strategies for addressing existing challenges and promoting pedagogical approaches that effectively cater to the needs of special needs students in Indonesia.